EFL Students’ Learning Engagement in The Post Pandemic Era - Khaerani, Nadya Shifa; Lintangsari, Alies Poetri; Gayatri, Putri (JEELS (Journal of English Education and Linguistics Studies), 2023)
The Indonesian government implemented online learning during the pandemic due to the spread of Covid-19.  Nowadays, the post-pandemic era, the application of offline learning has begun to be carried out again and is equipped with technology previously applied during online class. These sudden changes in the education sector certainly affect EFL students' learning engagement. This study was conducted to investigate students' perceptions of English learning engagement in offline classes and to determine whether there is significant difference in learning engagement between online and offline classroom environments. The researcher used a quantitative approach with an Indonesian-language survey questionnaire distributed online to 11th-grade students with 751 participants. The results showed that offline classrooms equipped with technology had a positive result and got significant differences in learning engagement in almost every dimension. These findings also implied that students' engagement on emotional engagement shows no significant differences because the dimension is more affected by the teacher's support and self-awareness in using the language itself. Further implications of this research reveal the need to explore more about EFL teaching techniques and technologies in the learning process to maximize students' engagement.